Neuro-Sufism as an Epistemological Bridge: Integrating Islamic Spirituality and Modern Science - Aprilia Musawamah; Suadi Sa’ad; Masykur Wahid; Ade Fakih Kurniawan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study examines the epistemological integration between Sufism and modern neuroscience in response to the persistent dichotomy between religious and scientific knowledge in contemporary Islamic thought. While previous studies have explored the psychological and functional dimensions of spirituality, few have systematically formulated an integrative epistemological framework connecting Sufi consciousness with neuroscientific theories of consciousness. This research aims to analyze the epistemology of consciousness in Sufism, examine neuroscientific perspectives on consciousness, and formulate Neuro-Sufism as an interdisciplinary epistemological paradigm. The study employs qualitative library research using a hermeneutic-philosophical approach to classical Sufi texts, particularly the works of Al-Ghazali and Ibn ‘Arabi, alongside neuroscientific theories proposed by Antonio Damasio and Andrew Newberg. The findings demonstrate that Al-Ghazali’s concept of qalb as the center of spiritual awareness corresponds to neuroscientific understandings of emotional-cognitive integration within the brain, particularly in relation to self-awareness and emotional regulation. Likewise, Ibn ‘Arabi’s notion of transcendent consciousness reflects dimensions of higher awareness that parallel contemporary discussions on altered states of consciousness and neuroplasticity. The study further finds that spiritual practices such as dhikr contribute not only to spiritual purification but also to measurable neurological changes associated with attention, emotional stability, and mental regulation. Based on these findings, this study formulates Neuro-Sufism as an integrative epistemological framework that unites revelation, reason, spiritual experience, and empirical neuroscience without reducing spirituality to biological mechanisms. This framework offers theoretical contributions to contemporary Islamic epistemology and practical implications for education, spirituality, and mental health.